Response of hya Expression to External pH in Escherichia coli - King, Paul W. (American Society for Microbiology, 1999)
The hya operon of Escherichia coli is composed of the genes which synthesize uptake hydrogenase isoenzyme 1 (Hyd1). Although hya expression and Hyd1 synthesis occur only under anaerobic conditions, Hyd1 is not essential for growth. In this study we used a hya′-′lacZ fusion to characterize parameters of anaerobic growth that maximize hya expression in an attempt to further elucidate Hyd1 function. We found that the expression pattern of hya followed a decline of external pH. In buffered media where the pH value was set, the onset of hya expression initiated earlier in growth and reached a greater peak level in acidic than in alkaline medium. When cultures expressing hya were shifted from acidic to alkaline conditions, hya expression was arrested; shifting from alkaline to acidic conditions stimulated hya expression. Maximal expression of hya under all growth conditions required the sigma factor RpoS and transcriptional regulators AppY and ArcA. In the absence of RpoS or AppY, the response of hya expression onset to external pH was evident and maximal hya levels remained greater in acidic than in alkaline medium. However, the absence of ArcA led to a diminished response of expression onset to external pH and the loss of elevated expression at an acidic external pH. The fermentation end product formate slightly altered hya expression levels but was not required for hya to respond to external pH. In contrast to hya expression, the onset of hyb operon expression, encoding uptake hydrogenase isoenzyme 2, was constitutive with respect to external pH. However, external pH did affect hyb expression levels, which, in contrast to hya, were maximal in alkaline rather than acidic medium.